(untitled) (Editora Impacto Científico, 2025)
This study analyzes the profound influence of Information Technology on Management Accounting, based on an integrative review of recent literature (2020-2025). The analysis reveals an evolutionary transformation in layers: ERP systems consolidate the database, BI and Big Data tools enhance analytical and predictive capacity, and automation via RPA and AI optimizes repetitive processes. This transition redefines the role of the management accountant, who evolves from a data compiler into a strategic business partner focused on interpreting information to guide management. However, challenges such as an analytical skills gap and new ethical issues emerge. It is concluded that the future relevance of the profession in the digital age depends on the synergy between human intelligence and technological capability to generate value. DOI: https://doi.org/10.56238/edimpacto2025.090-024